Risk factors for malignant mesothelioma in people with no known exposure to asbestos. Issue 5 (28th February 2017) - Musk, Bill; Gordon, Len; Alfonso, Helman; Reid, Alison; Olsen, Nola; Mina, Robin; Franklin, Peter; Peters, Susan; Brims, Fraser; Hui, Jennie; de Klerk, Nicholas
Abstract : Objectives: Malignant mesothelioma (MM) is a rare and generally fatal cancer, usually caused by asbestos, although about 5–10% of cases report no asbestos exposure. This study aimed to identify sources whereby people in Western Australia (WA) may be unknowingly exposed to asbestos or to other exposures which may cause MM. Methods: Cases with no known asbestos exposure were selected from the WA Mesothelioma Register (WAMR). Matched controls were selected from hospital patients admitted for conditions unrelated to asbestos. Occupational histories were coded by an industrial hygienist. Data were analyzed using conditional logistic regression. Results: Thirty‐eight MM participants and 134 controls were recruited. Risk of MM was increased (OR = 3.1, 95%CI 1.0–9.6) after no known, but likely, exposure to asbestos at work. Conclusions: Because of its extensive use, few people in WA have never been exposed to asbestos. Unrecognized exposure may cause most MM cases initially regarded as "no exposure." Am. J. Ind. Med. 60:432–436, 2017. © 2017 Wiley Periodicals, Inc.